EFEKTIVITAS MEDIA GAPOK DENGAN MODEL TGT UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN POLA KALIMAT PADA SISWA KELAS 3 SD - Hidayah, Nurul (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This study aims to test the effectiveness of GAPOK media with the TGT model to improve students' ability to compose sentence patterns. The research was conducted at SDN 3 Krasak with a total of 38 third grade students. The research method is quantitative with a quasi-experimental design. There are two classes, experimental and conventional classes. The results showed that learning with GAPOK media with the TGT model was quite effective. The results of the experimental class N-gain test obtained a Gain score of 0.781 in the medium category and 78.07% in the effective category. The results of the experimental class N-gain test obtained a gain score of 0.335 in the high category and 33.51% in the effective category. The results of this study can contribute that this media can be used as an effective learning media, it can be recommended in improving students' ability to compose sentence patterns.